A method to define the priority for maintenance and repair works of Italian motorway tunnels. Issue 1 (August 2021) - Barla, M; Barbero, M; Baralis, M; Insana, A; Milan, L; Rosso, E; Selleri, A; Marchiondelli, A; Mele, P; Tripoli, L; Zilli, L
Abstract: The construction of motorways in Italy dates back to 1921 and still lasts today. Along them there is a large number of tunnels, many of which have been in service for more than 50 years and have experienced various levels of decay due to aging. An extensive assessment and inspection plan is taking place finalized to highlight situations where maintenance and repair works are needed to guarantee the continuation of service in safe conditions and functionality. Due to the number of tunnels, the need arises to classify them and define priorities for intervention on the basis of a first assessment and of a robust and scientific-based tool to orientate the investments. This paper describes the methodology that was developed by the Authors for this purpose, assessing the attention level of every tunnel. The method relies on a quantitative approach that allows quantifying the risk based on five risk factors composed of a number of relevant parameters. Their relative interaction, which guided the scores assigned to each parameter, was assessed by applying the Rock Engineering System [2]. A number of examples of existing tunnels are shown to illustrate the application of the method and to draw conclusions about its validity and reliability.